Kemampuan Menulis Resensi Biografi Populer Melalui Model Problem Based Learning - Rafsanjani Rafsanjani (Journal on Education, 2024)
This study aims to improve the Ability to Write Popular Biography Reviews through the Problem Based Learning Model, especially for Students of the D-III Civil Engineering Study Program Class 2C Even Semester of the 2023-2024 Academic Year of the Pontianak State Polytechnic. This type of research uses the action research method with four components, namely planning, action, observation, and reflection. This classroom action research lasted for 3 stages, consisting of pre-cycle, cycle I, and cycle II. The method in this study is qualitative research. The subjects in this study were 29 Students of the D-III Civil Engineering Study Program Class 2C. The data collection technique in this study was in the form of tests and questionnaires, while the supporting technique was using documentation. The process and results of the study, namely the ability to write biographical reviews through the Problem Based Learning Model, can be seen in the pre-cycle stage, students only got a low score of 63.00. Then in the first cycle stage there was an increase of 74.00. Then in the final stage or cycle two there was a significant and satisfactory increase of 81.00. Thus, it can be concluded that the use of the Problem Based Learning model in writing biographical reviews has succeeded in improving students' ability to write biographical reviews.